2011
DOI: 10.1111/j.1526-4637.2011.01101.x
|View full text |Cite
|
Sign up to set email alerts
|

Liposuction May Reduce Pain in Dercum's Disease (Adiposis Dolorosa)

Abstract: The results suggest that liposuction might alleviate pain in patients with Dercum's disease. However, it is difficult to determine whether the effect is due to the actual surgery or to other factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 32 publications
1
27
0
1
Order By: Relevance
“…The first 53 consecutively-referred patients were later operated on with liposuction and the following 58 women with Dercum’s disease were recruited as controls to compare the effect of liposuction in the disease. The result of that study has been reported elsewhere [7]. All of the patients that were referred to this study were female.…”
Section: Methodssupporting
confidence: 56%
“…The first 53 consecutively-referred patients were later operated on with liposuction and the following 58 women with Dercum’s disease were recruited as controls to compare the effect of liposuction in the disease. The result of that study has been reported elsewhere [7]. All of the patients that were referred to this study were female.…”
Section: Methodssupporting
confidence: 56%
“…Based on our review of the literature and studies on 111 patients with Dercum’s disease [46-48] we propose that Dercum’s disease should be classified into (Table 1):…”
Section: Classificationmentioning
confidence: 99%
“…A number of patients treated with liposuction have been presented [46,70]. In all cases, suction-assisted liposuction was used.…”
Section: Management Including Treatmentmentioning
confidence: 99%
“…4) Psychological support: See lipedema (above). 5) Surgery: Liposuction is one of the accepted methods of treatment for DD [196,[255][256][257] resulting in decreased pain [258,259] . When asked specifically about liposuction in a series of 110 patients, 83 respondents (75.5%) reported having had liposuction; of these, 50.6% reported that the painful fat depots grew back [188] .…”
Section: Dd Treatment Recommendationsmentioning
confidence: 99%